2019
DOI: 10.1038/s41467-019-09871-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of locomotor speed and selection of active sets of neurons by V1 neurons

Abstract: During fast movements in vertebrates, slow motor units are thought to be deactivated due to the mechanical demands of muscle contraction, but the associated neuronal mechanisms for this are unknown. Here, we perform functional analyses of spinal V1 neurons by selectively killing them in larval zebrafish, revealing two functions of V1 neurons. The first is the long-proposed role of V1 neurons: they play an important role in shortening the cycle period during swimming by providing in-phase inhibition. The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 47 publications
5
94
2
Order By: Relevance
“…In order to selectively ablate dI6dmrt3a neurons, we generated Tg[dmrt3a:lRl-DTA] (DTA [diphtheria toxin A subunit]). The fish were crossed to Tg[hoxa9a-3 0 enhancer:Cre] (hereafter called Tg[hox:Cre]) in which Cre recombinase expression is localized to the trunk (Kimura and Higashijima, 2019). This enabled targeting of DTA expression to the spinal cord.…”
Section: Morphology Of Di6dmrt3a Neuronsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to selectively ablate dI6dmrt3a neurons, we generated Tg[dmrt3a:lRl-DTA] (DTA [diphtheria toxin A subunit]). The fish were crossed to Tg[hoxa9a-3 0 enhancer:Cre] (hereafter called Tg[hox:Cre]) in which Cre recombinase expression is localized to the trunk (Kimura and Higashijima, 2019). This enabled targeting of DTA expression to the spinal cord.…”
Section: Morphology Of Di6dmrt3a Neuronsmentioning
confidence: 99%
“…Tg[glyt2:lRl-GFP] and Tg[dmrt3a:loxP-DsRed-loxP-DTA (lRl-DTA)] transgenic fish were generated using the CRISPR/Cas9-mediated knock-in method with the hsp70 promoter (Kimura et al, 2014). Tg[hoxa9a-3 0 enhancer:Cre] was described in Kimura and Higashijima (2019).…”
Section: Transgenic Zebrafishmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies identified V1 interneurons marked by engrailed-1 expression and V2b interneurons defined by expression of Lhx3 and Gata3 as ipsilaterally projecting inhibitory interneurons that play contrasting roles in locomotor control. V1 interneurons seem to shorten the duration of swimming episodes and derecruit slow-muscle innervating MNs (Kimura and Higashijima, 2019), whereas V2b interneurons provide a break to locomotor speed (Callahan et al, 2019). How the combined activity of these populations shapes the rhythm of tail beats during swimming episodes, and whether their contributions change as fish transition from burst swimming to beat-and-glide swimming remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%